Prevalence of musculoskeletal pain in field hockey players of Maharashtra: a cross-sectional study - Khatavkar, Mayuri A.; Pawar, Shradha; Kedare, Sayali (International Journal Of Community Medicine And Public Health, 2025)
Background: Field hockey has its dynamic nature involving multidirectional movements which may lead to injuries. Thus, the study was aimed to find prevalence of pain and further categorizing with respect to gender, type of players and their playing positions, amongst hockey players. Methods: It was a cross-sectional observational study taken place amongst various hockey clubs and Maharashtra Hockey Association. 363 participants out of 700 of mean age (20.89±11.04 years) were recruited from various zones of Maharashtra, along with respective consent. Data was tabulated and analyzed using MS-Excel. Results: It was found highest in lower-back (34%) amongst the field hockey players. Based on gender, the most prevalent sites of pain were lower-back (22%) in males and neck (21%) in females. Lower back region seemed to be most prevalent in pain in both elite (42%) and recreational (29%) players. In elite players, most prevalent pain was seen as low back (46%) in males and that of bilateral hips (30%) in females. In recreational players, it was found that both genders reported prevalence of injury over lower back. (males- 25%, females- 33%). Based on play positions, it was found knee region in the goal-keepers and in lower-back of defenders get affected the most (47%). These numbers would help to filter out injury prone areas and to help in formulating preventive measures. Conclusions: It was concluded that the highest prevalence of pain was found in lower-back (34%).